Pertumbuhan dan Perkembangan Bibit Rhyncostylis retusa L. (Bl.) (Orchidaceae) pada Konsentrasi Fosfor (P) Berbeda - Nurfadilah, Siti (Center for Plant Conservation Bogor Botanic Garden, Indonesian Institute of Sciences, 2013)
Phosphorous (P) is one of the essential minerals for plant growth and development.Â The aim of this study is to investigate the effect of Phosphorous on Rhyncostylis retusa seedlings in in vitro culture and to investigate the optimum P concentration for growth and development of the plantlet. Protocorms derived from seed were inoculated on KC (Knudson C) media with a range of P concentrations (0 mM; 0.42 mM; 0.84 mM, and 1.2 mM). The result showed that phosphorus influenced the growth and the development of R. retusa seedlings. Growth and development of the seedlings were inhibited on control treatment (0 MM), while seedlings on P concentration of 0.42 mM; 0.84 mM, and 1.2 mM grew better.